(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Interview with teacher PHD Carlos Frederico Marés de Souza Filho, from Lawyers for Democracy, and with teacher PHD Eduardo Faria Silva, representative of the Union of Engineers of Paraná. Both led the creation and execution of Circus of Democracy, held in Curitiba, form august 5 to 15, 2016. The poles of Circo Zanchettini, transferred to Circus of Democracy, were planted in Santos Andrade Square and their canvases were wide open in defense of democracy and Against the coup Against President Dilma Rousseff. For 10 days, Circus of Democracy performed and received political Leaders, among them President Dilma Rousseff, cultural, union, student, women, indigenous and rural movements, Leading art and resistance. Hopeful for the resumption of democratic freedoms and with renewed strength to continue the fight, we present the interview witch comrades Carlos and Educardo, held in january 2023.